Characterisation of 'class A' polymer composites for the automotive industry - Schubel, Peter James (2004)
This thesis addresses problems associated with surface quality measurement and residual volatile organic compounds for composite laminates intended for use as cosmetic body parts based on unsaturated polyester resin containing shrinkage control additives. Surface quality measurement techniques were compared for composite laminates allowing for rapid characterisation and benchmarked to industrial standards. Thermal desorption and solvent elution techniques were used for the detection of residual volatiles with styrene and benzaldehyde being the main focus. The degree of conversion and residual volatiles were monitored for three peroxide initiators via a series of statistically developed experiments. This work highlighted the need for alternative shrinkage control methods. A novel approach was studied through the use of nano-scale silicates. An exfoliation process was developed with subsequent characterisation of thermal and mechanical properties for the nanocomposite. Finally, a series of hybrid matrices consisting of nanocomposite and low profile additive blends were monitored for effects on surface roughness, residual volatile levels and mechanical performance.